2021
DOI: 10.1128/msphere.00726-21
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Receptor Repertoire Analysis in Malaria-Naive and Malaria-Experienced Individuals Reveals Unique Characteristics of Atypical Memory B Cells

Abstract: Malaria, caused by Plasmodium parasites, still contributes to a high global burden of disease, mainly in children under 5 years of age. Chronic and recurrent Plasmodium infections affect the development of B cell memory against the parasite and promote the accumulation of atypical memory B cells (atMBCs), which have an unclear function in the immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Concerning the origin and clonality of atBCs, BCR sequencing analysis provided evidence of comparable SHM rates and clonal relationships between Pf- specific atBCs, actBCs, and MBCs, suggesting that these subsets originate from common affinity–matured B cell precursors. This is consistent with previous studies of bulk B cell subsets in malaria-exposed individuals in Mali ( 12 ), Kenya ( 10 ), and Uganda ( 39 ), but at odds with a study in Gabon that showed little evidence of clonal relationship between atBCs and MBCs ( 21 ).…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the origin and clonality of atBCs, BCR sequencing analysis provided evidence of comparable SHM rates and clonal relationships between Pf- specific atBCs, actBCs, and MBCs, suggesting that these subsets originate from common affinity–matured B cell precursors. This is consistent with previous studies of bulk B cell subsets in malaria-exposed individuals in Mali ( 12 ), Kenya ( 10 ), and Uganda ( 39 ), but at odds with a study in Gabon that showed little evidence of clonal relationship between atBCs and MBCs ( 21 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although the results of this experiment will require confirmation in additional individuals, this is the first analysis of its kind in a malaria-experienced person and will provide valuable insight into the molecular characteristics of the anti-PfMSP1 plasma antibody repertoire after life-long exposure to Pf . In a previous study, we generated B cell receptor sequencing (BCR-seq) data of antibody heavy chain variable regions of naïve B cells, classical MBCs, and atypical MBCs ( 43 ). The full BCR-seq data set and all sequences obtained from PfMSP1-specific MBCs were used to construct a personalized, donor-specific reference heavy chain antibody variable region sequence database.…”
Section: Resultsmentioning
confidence: 99%
“…cycle time. B cell receptor sequencing data was available from a previous study ( 43 ). Demultiplexing of sequence reads and the generation of consensus sequences for UMI groups were performed as outlined by Turchaninova et al using software tools MIGEC (v1.2.9) and MiTools (v1.5) ( 85 ).…”
Section: Methodsmentioning
confidence: 99%
“…These cells are characterized by the expression of inhibitory markers, and they can be activated by inflammatory signals, such as IFNγ and TLR-9 activation by parasite DNA (reviewed in [ 380 ]). Recent data suggests that AtMBCs or IgM producing MBCs may be part of a normal memory immune response in chronically exposed or vaccinated individuals and various questions remain relating to their development and functionality [ 359 , 363 , 380 382 ]. In in vitro co-cultures, AtMBCs increase and classical memory B cells contract in the presence of parasites [ 383 ].…”
Section: Twenty-first Century—turning Point In Malaria Researchmentioning
confidence: 99%